Investigation On Elasticity Rate Of Silver Nano-Particles-Filled Epoxy Conductive Ink - Salim, Mohd Azli; Mokhlis, Maizura; Omar, Ghazali; Rahim, N.A.A; Md. Saad, A. (Universiti Teknikal Malaysia Melaka, 2018)
This paper investigates the elasticity rate of silver nanoparticles-filled conductive ink with nano indentation tester.The nano indentation tester is used to measure the hardness value of the silver nanoparticle-filled epoxy conductive ink.Based on the results,silver nanoparticles with 90 %wt have the highest Young’s modulus as compare to the others.Thus,this nanoparticles have higher opportunity to retain its original shape.In addition, silver nanoparticles with 90 %wt also have the highest hardness,which is 3.07 Hv.